Perspective of Gender Equality in surah An-Nisa': 34 (Comparative Study of Tafsir At-Thabari and Tafsir Al-Azhar) - Karim, Roihan Muhammad Iqbal; Rhain, Ainur (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Religion is often characterized by gender inequality. Gender equality has always been a subject of controversy, especially in explaining, interpreting, and determining the law between women and men. At-Thabari and Buya Hamka have similarities and differences in interpreting surah an-Nisa': 34. This research aims to find out the interpretation of surah an-Nisa': 34 according to the classic and contemporary interpreters At-Thabari and Buya Hamka, looking for similarities and differences in the interpretations of At-Thabari and Buya Hamka, and knowing the relevance of gender equality in the perspective of surah an-Nisa': 34. This type of research uses library research. Then it is analyzed with a comparative descriptive method, carried out by analyzing, comparing, and checking data validity techniques to obtain research results in accordance with the objectives. The results of this study indicate that At-Thabari and Buya Hamka's thoughts on gender equality have similarities in interpreting surah an-Nisa': 34 regarding male authority over women, and there are differences in thinking based on surah An-Nisa: 34 regarding interpretative views. Differences in time, conditions, situations, and civilizations that influence them. Based on this research, it can also be concluded that surah an- Nisa': 34 emphasizes that Islam on several occasions exalts the position of men over women. Gender equality is part of Islamic values that apply universally.